A History of Research on Human Evolution in South Africa from 1924 to 2016 - John Francis Thackeray (Revue de Primatologie)
South Africa has a rich palaeo-anthropological heritage. The very first Plio-Pleistocene specimen of Australopithecus, from the site of Taung, was described by Raymond Dart in 1925. In 1936 the first australopithecine was discovered at the site of Sterkfontein. Thereafter there was an increase in the number of hominin specimens attributed to Australopithecus, Paranthropus or early Homo from Sterkfontein, Swartkrans and Kromdraai (as reported by Robert Broom and John Robinson after 1947). The pioneering work was continued by Bob Brain, Elisabeth Vrba, Phillip Tobias, Ron Clarke, Francis Thackeray and their teams. Within recent decades many important discoveries have been made by young palaeontologists such as Dominique Gommery and Frank Sénégas (Bolt's Farm Cave System), José Braga (Kromdraai), Travis Pickering (Swartkrans), Lee Berger (Malapa associated with A. sediba and Rising Star associated H. naledi), Colin Menter (Drimolen) and a growing number of young individuals with access to micro CT scanners and synchrotrons which permit studies of internal anatomy. This article presents a summary of the history of palaeo-anthropological fieldwork and research in South Africa within a period of almost 100 years.